2015
DOI: 10.18632/oncotarget.6363
|View full text |Cite
|
Sign up to set email alerts
|

ERK8 is a novel HuR kinase that regulates tumour suppressor PDCD4 through a miR-21 dependent mechanism

Abstract: Programmed cell death 4 (PDCD4) is a tumour suppressor implicated in cancer development and progression and was recently identified as a repressor of cap-independent translation of specific genes involved in the regulation of apoptosis. We show that the RNA-binding protein HuR binds to the PDCD4 3′UTR to protect it from miR-21-induced silencing. However, following H2O2 treatment, PDCD4 mRNA is degraded via miR-21 binding. Importantly, we identify HuR as a novel substrate of the ERK8 kinase pathway in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Interestingly, pretreatment of CMs with stressed CPC-derived exosomes (or miR-21 mimic) rescued the decrease of miR-21 and exhibited decreased apoptosis when exposed to oxidative stress [ 43 ]. These findings support the antiapoptotic role of miR-21 in cytoprotection, which further studies revealed to occur by directly targeting PDCD4—a promoter of tumor cell apoptosis [ 81 ]. Similarly, exosomes isolated from mouse CPCs which demonstrated protection against oxidative stress-induced apoptosis were found to be enriched in miR-451/−144 [ 82 ].…”
Section: Exosomes and Mirnassupporting
confidence: 71%
“…Interestingly, pretreatment of CMs with stressed CPC-derived exosomes (or miR-21 mimic) rescued the decrease of miR-21 and exhibited decreased apoptosis when exposed to oxidative stress [ 43 ]. These findings support the antiapoptotic role of miR-21 in cytoprotection, which further studies revealed to occur by directly targeting PDCD4—a promoter of tumor cell apoptosis [ 81 ]. Similarly, exosomes isolated from mouse CPCs which demonstrated protection against oxidative stress-induced apoptosis were found to be enriched in miR-451/−144 [ 82 ].…”
Section: Exosomes and Mirnassupporting
confidence: 71%
“…PDCD4, PTEN, RECK and Bcl-2 can be regulated by miR-21 in many cell types. These genes are critical for promoting cell proliferation, differentiation and migration[ 63 65 ]. PTEN has been reported to be a target gene of miR-21 in many cell types[ 3 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, very few substrates have been identified for ERK8 homologs. The only known cellular substrate of HsERK8 to date is the RNA binding protein HuR, 28 which is encoded by the ELAVL1 gene. HuR binds to the 3′UTR of the PDC4 tumor suppressor to protect it from miRNA 21 mediated gene silencing.…”
Section: Discussionmentioning
confidence: 99%